Konseling Kelompok Berbasis Cybercounseling Pendekatan Rational Emotive Behaviour Theraphy (REBT) untuk Meningkatkan Kontrol Diri Siswa - Ifan Setiawan; Heru Mugiarso (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2021)
This study aims to determine the effect of group counseling services based on rational emotive behavior therapy with cybercounseling approach on students' self-control. This research design is pre-experimental research with one group pre-test and post-test research design. The Participants of this study was 8 students recruited using the criteria of sampling technique. The data was collected using a psychological scale that was developed based on indicators from other studies which analyzed using the Wilcoxon analysis technique. The results showed that the level of self-control of students who were given group counseling services group counseling services based on rational emotive behavior therapy with cybercounseling approach increased by 23.36%. This study also proved that group counseling services based on group counseling services based on rational emotive behavior therapy with cybercounseling approach affect students' self-control.